2010
DOI: 10.5194/angeo-28-1207-2010
|View full text |Cite
|
Sign up to set email alerts
|

Substorm-related thermospheric density and wind disturbances derived from CHAMP observations

Abstract: Abstract. The input of energy and momentum from the magnetosphere is most efficiently coupled into the high latitude ionosphere-thermosphere. The phenomenon we are focusing on here is the magnetospheric substorm. This paper presents substorm related observations of the thermosphere derived from the CHAMP satellite. With its sensitive accelerometer the satellite can measure the air density and zonal winds. Based on a large number of substorm events the average high and low latitude thermospheric response to sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
69
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 37 publications
12
69
0
Order By: Relevance
“…More details of this study can be found in Ritter et al (2010). Interestingly, in the post-midnight sector (bin 3) only marginal substorm-related thermospheric variations are recorded.…”
Section: Substorm Effects On the Thermospherementioning
confidence: 99%
See 3 more Smart Citations
“…More details of this study can be found in Ritter et al (2010). Interestingly, in the post-midnight sector (bin 3) only marginal substorm-related thermospheric variations are recorded.…”
Section: Substorm Effects On the Thermospherementioning
confidence: 99%
“…Ritter et al (2010) have deduced a mean propagation speed of 650 m/s from their observations. Furthermore they report a westward deflection of the travel path.…”
Section: Substorm Effects On the Thermospherementioning
confidence: 99%
See 2 more Smart Citations
“…When interpreting these average values, we have to keep in mind that substorms are discrete events. It would be more appropriate to synchronize the nighttime current measurements with the occurrence and phase of a substorm, as was done, e.g., by Ritter et al (2010). Then the obtained FAC and Hall current measurements could be better related to the processes operating during substorms.…”
Section: Substorm Electrojetmentioning
confidence: 99%